(untitled) (ModaPalavra e-periódico, 2021)
In the first post-lockdown commercial reopening that aimed to minimize the contagion of Sars-CoV-2, in several world capitals, we witnessed tumultuous scenes of agglomeration caused by anxious consumers. They awaited the opening of stores of major fashion brands and, as a result, generated relevant revenue for these companies. Based on the thinking of philosophers: Lipovetsky, Deleuze and Foucault, we promote a reflection on such behavior. Considering the threatening context and, at that time, the exposure to a risk of unknown proportions, we asked ourselves: what drives this desire to consume? We deal with the logic that governs the capitalist and fashion systems, whose historical relationship gave rise to a desiring consumer. Fleeing from dichotomous thinking, we consider that the reason-system is a condition constitutively produced by the subject, which has its maximum expression in the fashion culture. We conclude that, as fashion culture is the culture of Being, this was sought as an essential consumption.